2017
DOI: 10.1590/0103-6440201700737
|View full text |Cite
|
Sign up to set email alerts
|

Cytotoxic Effect of Thymus caramanicus Jalas on Human Oral Epidermoid Carcinoma KB Cells

Abstract: Identifying new chemotherapeutic agents with fewer side effects is a major concern for scientists today. Thymus caramanicus Jalas (Lamiaceae family) is one of the species of Thymus that grows wild in different regions of Iran. Traditionally, leaves of this plant are used in the treatment of diabetes, arthritis and cancer. Here was investigated the cytotoxic property of Thymus caramanicus essential oil and extract in human oral epidermoid carcinoma KB cells. Cell viability was measured by MTT and neutral red as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 24 publications
0
8
0
2
Order By: Relevance
“…has been significantly increased with IC50 of 80.7 μg·mL −1 , 70.3 μg·mL −1 and 100.2 μg·mL −1 [ 45 ]. A recent study has shown the cytotoxic effect of Thymus caramanicus Jalas, a common species in Iran, against KB human oral epidermoid carcinoma [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…has been significantly increased with IC50 of 80.7 μg·mL −1 , 70.3 μg·mL −1 and 100.2 μg·mL −1 [ 45 ]. A recent study has shown the cytotoxic effect of Thymus caramanicus Jalas, a common species in Iran, against KB human oral epidermoid carcinoma [ 46 ].…”
Section: Resultsmentioning
confidence: 99%
“…The main components were carvacrol (51.0%), thymol (20.84%), borneol (6.80%), cymene (6.25%), γ-terpinene (5.50%), and β-myrcene (1.63%). The IC 50 value was 0.44 μL/mL in KB cell line (oral carcinoma) [19].…”
Section: Thymusmentioning
confidence: 97%
“…Indeed, it has been reported that pine, lime and eucalyptus essential oils possess antioxidant proprieties and act in reducing reactive oxygen species (ROS) in LPS-activated alveolar macrophages isolated from chronic pulmonary disease patients [ 22 ]. Thyme essential oil possesses anti cancer proprieties and act in reducing proliferation of oral carcinoma cells [ 23 ], while cinnamon essential oil exhibits anti tumor effects in HEp-2 cells by suppressing the expression of epidermal growth factor receptor-tyrosine kinase.…”
Section: Introductionmentioning
confidence: 99%